PENGARUH CASH HOLDING DAN FINANCIAL LEVERAGE TERHADAP INCOME SMOOTHING: CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERATING - Zidane Bertand Arya; Imang Dapit Pamungkas (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
In a company, financial statements are vital because they have a role as a result of operational activities in a company in a period. Financial statements also have a function as an illustration of a company regarding the good or poor capabilities of the company. One of the crucial accounts in assessing the company's performance is profit. In fact, the work on Income Smoothing causes some speculation, some think that Income Smoothing is detrimental to users of financial statements because it does not explain the content of reasonable reports on the company's financial position. Meanwhile, other parties think that Income Smoothing is reasonable because it does not violate accounting standards. The purpose of this observation is to find out whether cash holding and financial leverage are able to affect income smoothing, as well as to find out whether corporate governance variabels are able to moderate cash holding and financial leverage on income smoothing. The population of this study is stateowned companies in 2016-2021 a total of 48 companies with 6 years, selecting samples using the purposive sampling method and obtaining samples with a total of 108. This research found that the cash holding variabel is able to affect income smoothing, financial leverage is unable to affect income smoothing, corporate governance is able to moderate or reduce the influence between cash holding and income smoothing, corporate governance is unable to moderate or reduce the influence between financial leverage and income smoothing. The software used for data processing is SPSS Statistics 20.